2020
DOI: 10.21203/rs.3.rs-23463/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Articular chondrocyte-derived extracellular vesicles promote cartilage differentiation of human umbilical cord mesenchymal stem cells by activation of autophagy

Abstract: Background: Umbilical cord mesenchymal stem cell (HUCMSC)-based therapies were previously utilised for cartilage regeneration because of the chondrogenic potential of MSCs. However, chondrogenic differentiation of HUCMSCs is limited by the administration of growth factors like TGF-β that may cause cartilage hypertrophy. It has been reported that extracellular vesicles (EVs) could modulate the phenotypic expression of stem cells. However, the role of human chondrogenic-derived EVs (C-EVs) in chondrogenic differ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…The fresh human umbilical cords were acquired under sterile conditions from healthy donors following full-term cesarean operation in The First Affiliated Hospital of Guangxi Medical University. Extraction of the MSCs from the human umbilical cords as described previously [ 48 ]. Briefly, the blood vessels in the umbilical cords are first removed and subsequently minced to obtain Wharton's jelly.…”
Section: Methodsmentioning
confidence: 99%
“…The fresh human umbilical cords were acquired under sterile conditions from healthy donors following full-term cesarean operation in The First Affiliated Hospital of Guangxi Medical University. Extraction of the MSCs from the human umbilical cords as described previously [ 48 ]. Briefly, the blood vessels in the umbilical cords are first removed and subsequently minced to obtain Wharton's jelly.…”
Section: Methodsmentioning
confidence: 99%
“…The reported size and surface markers of human articular chondrocyte-derived EVs are similar to that of other cell-derived EVs. Although some reports highlighted that heterotrimeric G protein, HSP70 and 90, and members of the tetraspanin family such as CD9, CD63 and CD81 were not detected in the proteome of articular cartilage-derived EVs 52 , 53 , emerging research confirmed that CD9, CD63, and TSG101 proteins were expressed on chondrocyte-derived EVs 54 - 57 . Meanwhile, the content of EVs varies along with different types of tissues.…”
Section: The Biological and Pathophysiological Characteristics Of Evsmentioning
confidence: 99%
“…The thermocycling conditions were set at 95 C for 600 s, 45 cycles of 95 C for 10 s, and followed by 60 C for 1 min, as per methods described previously. 36 The expression level of the key genes was normalized to that of glyceraldehyde phosphate dehydrogenase (GAPDH) and was analyzed utilizing the comparative method 2 ÀDDCt . The PCR primers used in this study are listed in Table 2.…”
Section: Quantitative Real-time Pcr Assaymentioning
confidence: 99%